Application of FDG-PET/CT in Radiation Oncology - Jun eLi; Ying eXiao (Frontiers in Oncology, 2013)
Positron emission tomography (PET)/computed tomography (CT), which combines the advantages of high sensitivity and specificity of PET and high resolution of CT, is a unique tool for cancer management. PET/CT has been widely used in cancer diagnosis and treatment. The article reviews the recent applications of PET/CT in radiation oncology, with a focus on FDG-PET/CT, addressing the applications in treatment planning and treatment response assessment of radiation therapy.